Flow Cytometric Analysis of T, B, and NK Cells Antigens in Patients with Mycosis Fungoides - Serkan Yazıcı; Emel Bülbül Başkan; Ferah Budak; Barbaros Oral; Şaduman Balaban Adim; Zübeyde Ceylan Kalin; Güven Özkaya; Kenan Aydoğan; Hayriye Saricaoğlu; Şükran Tunali (Journal of Immunology Research)
We retrospectively analyzed the clinicopathological correlation and prognostic value of cell surface antigens expressed by peripheral blood mononuclear cells in patients with mycosis fungoides (MF). 121 consecutive MF patients were included in this study. All patients had peripheral blood flow cytometry as part of their first visit. TNMB and histopathological staging of the cases were retrospectively performed in accordance with International Society for Cutaneous Lymphomas/European Organization of Research and Treatment of Cancer (ISCL/EORTC) criteria at the time of flow cytometry sampling. To determine prognostic value of cell surface antigens, cases were divided into two groups as stable and progressive disease. 17 flow cytometric analyses of 17 parapsoriasis (PP) and 11 analyses of 11 benign erythrodermic patients were included as control groups. Fluorescent labeled monoclonal antibodies were used to detect cell surface antigens: T cells (CD3+, CD4+, CD8+, TCRαβ+, TCRγδ+, CD7+, CD4+CD7+, CD4+CD7−, and CD71+), B cells (HLA-DR+, CD19+, and HLA-DR+CD19+), NKT cells (CD3+CD16+CD56+), and NK cells (CD3−CD16+CD56+). The mean value of all cell surface antigens was not statistically significant between parapsoriasis and MF groups. Along with an increase in cases of MF stage statistically significant difference was found between the mean values of cell surface antigens. Flow cytometric analysis of peripheral blood cell surface antigens in patients with mycosis fungoides may contribute to predicting disease stage and progression.